Low-temperature biosynthesis of silver nanoparticles using mango leaf extract: catalytic effect, antioxidant properties, anticancer activity and application for colorimetric sensing. (6th September 2018) - Samari, Fayezeh; Salehipoor, Hossein; Eftekhar, Ebrahim; Yousefinejad, Saeed
Abstract : Aqueous mango leaf extract was used as a reducing and capping agent for the biosynthesis of silver nanoparticles (AgNPs) via a single-step, low cost and green process. Abstract : Aqueous mango leaf extract was used as a reducing and capping agent for the biosynthesis of silver nanoparticles (AgNPs) via a single-step, low cost and green process. The formation of nanoparticles was investigated under various experimental conditions such as pH, concentration of Ag + solution, quantity of leaf extract, temperature and incubation time. The AgNPs synthesized under optimum conditions were characterized by UV-Vis, XRD, TEM and FTIR to verify the production, crystallinity, morphology and surface bio-functionalities of the biosynthesized AgNPs. The catalytic activities of the as-synthesized AgNPs in the reduction of azo dyes, methylene blue (MB) and rhodamine B (RhB) by NaBH4 were studied. Furthermore, the biological activities of these nanoparticles were confirmed based on their anti-cancer effects by MTT assay against HCT116 and SW480 human colon cancer cell lines and antioxidant capacity by the ferric reducing antioxidant power (FRAP) assay. Moreover, as an application in chemical sensing, colorimetric studies of the as-synthesized AgNPs showed selective sensing of toxic Hg 2+ ion in water without further modification. This sensor had a wide linear dynamic range from 0.2 to 103.7 ppm with the aid of principal component analysis (PCA), followed by an artificial neural network (ANN). Finally, it is worthy to note that the effective catalytic and mercury detecting properties coupled with low-cost and low-toxicity can make these AgNPs attractive choices for wastewater management systems.